2005
DOI: 10.1021/ja053613q
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals Complexes of Polar Aromatic Molecules:  Unexpected Structures for Dimers of Azulene

Abstract: Full geometry optimizations at the dispersion corrected DFT-BLYP/TZV2P level of theory have been performed for dimers of azulene that may serve as a model system for the van der Waals complexes of polar pi systems. The structures and binding energies for 11 dimers are investigated in detail. The DFT-D interaction energies have been successfully checked against results from the accurate SCS-MP2/aug-cc-pVTZ approach. Out of the nine investigated stacked complexes, eight have binding energies larger than 7.4 kcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 52 publications
4
69
0
2
Order By: Relevance
“…The most widely applied and very well tested method is DFT-D 9 (with BLYP 18,19 and PBE 20 functionals), which proved high accuracy in many different applications. [21][22][23][24] After two years of careful testing and validation, however, knowledge of a few shortcomings of the original DFT-D method accumulated, which will be also addressed in the present work:…”
Section: Introductionmentioning
confidence: 99%
“…The most widely applied and very well tested method is DFT-D 9 (with BLYP 18,19 and PBE 20 functionals), which proved high accuracy in many different applications. [21][22][23][24] After two years of careful testing and validation, however, knowledge of a few shortcomings of the original DFT-D method accumulated, which will be also addressed in the present work:…”
Section: Introductionmentioning
confidence: 99%
“…49 They found that the most stable structure for the azulene neutral dimer is not an antiparallel -stacked geometry but an unexpected -stacked geometry where the two seven-membered rings are located almost on top of each other and the long molecular axes are rotated against each other by 130°. 49 They found that the most stable structure for the azulene neutral dimer is not an antiparallel -stacked geometry but an unexpected -stacked geometry where the two seven-membered rings are located almost on top of each other and the long molecular axes are rotated against each other by 130°.…”
Section: F Conditions For the Formation Of Isomer Ii-1/ii-2mentioning
confidence: 99%
“…47 Further examples for accurate results on related molecules can be found in Refs. [48][49][50]. Recently, Rahman and colleagues 51 have investigated nucleobases on graphene using several variants of vdW corrections.…”
mentioning
confidence: 99%